“PENA EMAS” Pencegahan Pernikahan Dini untuk Eliminasi Stunting Menuju Anak Sehat - Sri Atikah; Herawati Bin Sali; Winta Soamole; Paramita Arsyad; Jaswal Fataruba; I Gede Sudiantara; Mahdia Maylav Aisha Masihor (Lembaga Pengembangan Kinerja Dosen, 2025)
Early marriage remains a significant issue contributing to the high prevalence of stunting in Indonesia, particularly in rural areas. The lack of awareness among adolescents and parents regarding the negative impacts of early marriage and the importance of proper nutrition is a major contributing factor. The PENA EMAS (Early Marriage Prevention for Stunting Elimination Towards Healthy Children) program was implemented in Tanjung Buaya Village as part of the KKN-T Posko 22 UNIMMAN initiative to raise public awareness about the dangers of early marriage and its link to stunting risk. This program utilized three main stages: preparation, implementation, and evaluation. Activities included educational sessions, adolescent health screenings, local vegetable planting initiatives, and interactive media such as podcasts and educational competitions. The evaluation results showed an increase in community awareness of family planning and nutrition fulfillment, with five adolescents identified as having anemia based on hemoglobin (Hb) level tests. The conclusion of this program is that community-based educational interventions with participatory approaches can enhance awareness among adolescents and parents in preventing early marriage and reducing stunting risk. Recommended follow-up actions include regular health check-ups, adolescent mentoring, and the empowerment of Youth Ambassadors for Stunting Prevention to ensure the program’s sustainability.